Robust Fault Diagnosis for a Quadrotor with Actuator Fault - P. Nguyen, N.; K. Hong, S. (International Journal of Engineering and Technology, 2018)
Background/Objectives: Fault diagnosis (FD) is a main role in active fault tolerant control system. It can not only determine the location but also estimate the magnitude of fault.Methods/Statistical analysis: This article presents an adaptive fault diagnosis approach for a quadrotor with a simulated actuator fault. Firstly, the dynamics of the quadrotor are considered as a state space model. The magnitude of fault is identified through an adaptive law. Designed matrices and parameters are solving by linear matrix inequalities (LMI).Findings: Unlike previous studies, the present method can determine time-varying actuator faults with disturbances consideration.Improvements/Applications: Simulation results demonstrate that proposed method can estimate time-varying faults with high accuracy.Â Â